2000
DOI: 10.1111/1467-8624.00231
|View full text |Cite
|
Sign up to set email alerts
|

Same Beginnings, Different Stories: A Comparison of American and Chinese Children's Narratives

Abstract: This study examined social, emotional, and cognitive characteristics of American and Chinese children's narratives. Twenty-four American and 26 Chinese 6-year-old children participated. Each child was interviewed individually twice with a 1-week delay interval. During the two interviews, children were asked to tell 11 stories prompted by pictures and standard verbal leads and to recount 7 emotional memories. Content analyses were performed on children's stories and memories. In line with predictions, findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
2
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(141 citation statements)
references
References 62 publications
1
131
2
7
Order By: Relevance
“…Chinese students tended to provide briefer reports of general and routine collective events that were also emotionally neutral. Similar cultural differences in the content of autobiographical memories have been observed in preschool children (e.g., Han, Leichtman, & Wang, 1998;Wang, 2004;Wang & Leichtman, 2000). Interestingly, culture appears to affect not only the linguistic expression and content of event memories but also the perspective from which events that are encoded.…”
Section: The Self Sociolinguistic Interactions and Culturesupporting
confidence: 54%
“…Chinese students tended to provide briefer reports of general and routine collective events that were also emotionally neutral. Similar cultural differences in the content of autobiographical memories have been observed in preschool children (e.g., Han, Leichtman, & Wang, 1998;Wang, 2004;Wang & Leichtman, 2000). Interestingly, culture appears to affect not only the linguistic expression and content of event memories but also the perspective from which events that are encoded.…”
Section: The Self Sociolinguistic Interactions and Culturesupporting
confidence: 54%
“…Lee and his colleagues have consistently found that Chinese and Canadian children and adults differ in moral judgments of lying in modesty situations Lee, Cameron, Xu, Fu, & Board, 1997;Lee, Xu, Fu, Cameron, & Chen, 2001): Chinese children gave negative ratings to individuals who told the truth about their own good deed and positive ratings to those who lied about them, whereas Canadian participants did the opposite, suggesting that the ratings of the Chinese children reflect the influence of a Chinese cultural emphasis on self-effacement and modesty (Bond, 1986). individuals contrast, the ratings of the Canadian participants reflect a Canadian cultural appreciation of promoting self-confidence and self-esteem, somewhat similar to that of American children (Wang & Leichtman, 2000).Lee and his collaborators further suggested that this cross-cultural effect is rooted in those societies' differential emphasis on the relative importance of groups versus individuals regarding social interaction in general and communication in particular Lee et al, , 2001. They suggested that, although both the Canadian and Chinese cultures encourage honesty and discourage lying, the goals for interpersonal information exchange and related conventions are dramatically different in these two countries.…”
mentioning
confidence: 73%
“…First, we compared across the five reasons for remembering to examine whether some reasons were more likely to be reported than other reasons in a given context or for memories of a given theme. For example, this analysis would This method assimilates self-projection techniques that allow participants to freely express their thoughts and feelings when reporting their memories (Li & Wang, 2004;Wang & Leichtman, 2000). The thought-about prompt stated, "At night Heather (Tom) is in her (his) dorm alone.…”
Section: Resultsmentioning
confidence: 99%